AN ANALYSIS OF CHARACTER EDUCATION VALUES IN THE 2013 CURRICULUM ENGLISH TEXTBOOK OF THE TENTH GRADE STUDENTS - Mutiara Zein; Sumarsih Sumarsih; Indra Hartoyo (Universitas Negeri Medan, 2020)
This study was descriptive-qualitative approach using content analysis. The data used in this study were in the forms of texts in the textbook. Some steps were undertaken during the data collection: reading the texts carefully, understanding specific parts related to the research focus intensively, marking certain parts related to the research focus, making a description of the data and inserting the data into the table. The subjects were 10 texts in English textbook entitled Bahasa Inggris untuk SMA/MA/SMK/MAK Kelas X. The objects were the 18 characters described by Kemendiknas. The results showed that there were two points of findings discussed in this research. First, related to the occurrence of characters, Hard work character was the most dominant character found in the texts with 8 data or 19.04%. It implied that the author wanted wants to raise the students’ effort of students to other human..Second, related to the techniques of integrating characters, there were two techniques found in the texts, namely explicit and implicit technique. The implicit technique was more dominant in the texts with 24 data or 57.15%. This result showed that the author seemed to pay attention to the cognitive and affective aspects of the students in which at their age, they have been able to think critically and to understand the implied meaning.Keywords: characters, techniques of integrating characters, texts